Analysis and Design for a Horizontal Gasifier: Review Paper - Taher, Mayaf Mardan; Mahmood, Raid Ahmed (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The increasing demand for sustainable energy solutions has driven more research into alternative energy sources, including biomass-derived methane. This review paper discusses the analysis and design considerations of horizontal gasifiers in the context of efficient methane production and waste management. It covers the technical, environmental, and economic aspects of gasification technologies, underlining the role of fluidized bed systems and CFD modeling in optimizing combustion processes. Advanced gas collection systems, innovative design configurations, and catalytic enhancements have been discussed as being important for improving methane yield and reducing emissions. The paper also discusses various new trends in hydrothermal gasification and direct methanation, with much emphasis on the need for interdisciplinary approaches to overcome existing biomass conversion technology challenges. It indicates the vital contribution that horizontal gasifiers make in the production of renewable energy and to global sustainability.